MENDEFINISIKAN NILAI PERUSAHAAN MELALUI GREEN INVESTMENT DAN ECO- EFFICIENCY: STUDI KASUS DENGAN CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN - Sari Putri Pertiwi; Rina Nopianti; Rihand Akbar Cahyanti (Gapenas Publisher, 2025)
The recent fluctuation of stock prices in the capital market reflects growing investor uncertainty toward the domestic market. This is driven by concerns over fiscal deficits, the depreciation of the rupiah, and volatile global sentiment, all of which collectively affect firm value. This study aims to analyze the influence of green investment, eco-efficiency, and corporate governance on firm value, with firm size acting as a moderating variable. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. A quantitative approach was employed using purposive sampling, resulting in a sample of 10 energy companies with 50 firm-year observations from secondary data in annual reports. Hypothesis testing was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS software. The findings reveal that green investment and corporate governance have a positive influence on firm value, while eco-efficiency does not. Furthermore, firm size strengthens the relationship between both green investment and corporate governance with firm value, but it fails to moderate the relationship between eco-efficiency and firm value. This research provides significant implications for companies, especially in the energy sector, to actively integrate sustainability practices. Firms are encouraged to increase investment in impactful green initiatives and strengthen board structures by enhancing the proportion of independent commissioners to improve firm value.